2010
DOI: 10.1158/1535-7163.mct-10-0338
|View full text |Cite
|
Sign up to set email alerts
|

Ranpirnase (Frog RNase) Targeted with a Humanized, Internalizing, Anti–Trop-2 Antibody Has Potent Cytotoxicity against Diverse Epithelial Cancer Cells

Abstract: Ranpirnase (Rap), an amphibian RNase, has been extensively studied both preclinically and clinically as an antitumor agent. Rap can be administered repeatedly to patients without any untoward immune response, with reversible renal toxicity reported to be dose limiting. To enhance its potency and targeted tumor therapy, we describe the generation of a novel IgG-based immunotoxin, designated 2L-Rap(Q)-hRS7, comprising Rap (Q), a mutant Rap with the putative N-glycosylation site removed, and hRS7, an internalizin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 48 publications
1
40
0
Order By: Relevance
“…1). Ranpirnase is the smallest member of the ribonuclease (RNase A) superfamily, and appears to be a promising drug with broad clinical application in tumor treatment due to its moderate cytotoxicity, unique synergy, low immunogenicity and few side effects (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Between 1996 and 2004, Tamir Biotechnology, Inc. (formerly Alfacell Corporation) successively conducted clinical investigations regarding the effects of ranpirnase on breast cancer, pancreatic cancer, renal cell carcinoma, non-small cell lung cancer and malignant mesothelioma, for which the therapeutic effect was the most significant with few side effects.…”
Section: Introductionmentioning
confidence: 99%
“…1). Ranpirnase is the smallest member of the ribonuclease (RNase A) superfamily, and appears to be a promising drug with broad clinical application in tumor treatment due to its moderate cytotoxicity, unique synergy, low immunogenicity and few side effects (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Between 1996 and 2004, Tamir Biotechnology, Inc. (formerly Alfacell Corporation) successively conducted clinical investigations regarding the effects of ranpirnase on breast cancer, pancreatic cancer, renal cell carcinoma, non-small cell lung cancer and malignant mesothelioma, for which the therapeutic effect was the most significant with few side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Onconase, which is derived from Rana pipiens, and RC-RNase, which is derived from Rana catesbeiana, each belong to the RNase A superfamily (9,10). RC-RNase and Onconase have been revealed to demonstrate antitumor activity (10)(11)(12)(13). Previous studies have reported that RC-RNase is able to exert cytotoxic effects in various tumor cells, including cervical cancer, leukemia, hepatoma and breast cancer cells (11,(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, numerous studies have indicated that RC-RNase is able to trigger distinct cell death mechanisms in various tumor cell types (10,11,14,17). By contrast, previous studies have also revealed that Onconase can exert antitumor activities in numerous tumor cells, including cervical, breast, colon, pancreatic and prostate cancer cells (12,(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…ONC is the smallest member of the ribonuclease A (RNase A) family (Porta et al, 2008) and is considered unique since it has entered clinical trials (Darzynkiewicz et al, 1988;Ardelt et al, 1991). Once ONC is internalized and sorted to the cytosol, it could degrade the target tRNA to inhibit protein synthesis (Chang et al, 2010); however, the mechanism of its cytotoxicity is not completely understood. The company Timair (formerly known as Alfacell) has successively carried out I-III phase clinical trials of ONC on breast cancer, pancreatic cancer, non-small cell lung cancer, and malignant melanoma (Tian et al, 2010).…”
Section: Introductionmentioning
confidence: 99%